Chloroquine anticancer activity is mediated by autophagy-independent effects on the tumor vasculature - Maes, Hannelore (Mol Cell Oncol, 2015)
Chloroquine is used clinically as an autophagy blocker to potentiate anticancer treatments. However, whether chloroquine acts solely through autophagy-dependent and cancer cell autonomous mechanisms has remained elusive. In a recent study we found that chloroquine reduced intratumoral hypoxia and metastasis, while improving chemotherapy response, largely through an autophagy-independent, NOTCH1-reliant mechanism of tumor vessel normalization.